2013
DOI: 10.12659/msm.883776
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference. metabolic syndrome and obstructive sleep apnea syndrome; Evaluation of possible linkage

Abstract: BackgroundThis study was performed to evaluate neck circumference (NC) and metabolic syndrome (MS) parameters in severe and non-severe (mild-moderate) obstructive sleep apnea syndrome (OSAS) patients according to apnea-hypopnea index (AHI).Material/MethodWe enrolled 44 patients diagnosed with OSAS based on overnight polysomnography. The diagnosis of OSAS was based on AHI. Apnea is a pause of airflow for more than 10 seconds. and hypopnea is a decrease of airflow for more than 10 seconds and oxygen desaturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 33 publications
5
17
1
Order By: Relevance
“…Several recent studies showed correlations of AHI with BMI, neck, and waist circumference, which is consistent with our study [22, 23, 39, 40]. However, there are mixed reports on better correlates, with few studies showing neck circumference as better correlated with AHI [23, 24, 39, 40], and others showing waist circumference as a better correlate [22, 41], findings which are consistent with our study. In addition, there are a few studies where BMI values are better correlates of AHI than waist and neck circumferences [42, 43].…”
Section: Discussionsupporting
confidence: 93%
“…Several recent studies showed correlations of AHI with BMI, neck, and waist circumference, which is consistent with our study [22, 23, 39, 40]. However, there are mixed reports on better correlates, with few studies showing neck circumference as better correlated with AHI [23, 24, 39, 40], and others showing waist circumference as a better correlate [22, 41], findings which are consistent with our study. In addition, there are a few studies where BMI values are better correlates of AHI than waist and neck circumferences [42, 43].…”
Section: Discussionsupporting
confidence: 93%
“…The reported figures of mean NC (men 43.2 cm vs. women 40.6 cm� by Ho et al �2011�. 16 Similar findings were observed by Ahbab et al (2013), that mean value of NC among men were significantly greater com� pared to women �P < 0.001�. 14 Apart from NC per se, we found that when corrected for height �NC/Ht� as a predic� tor for severity of OSA, MLR analysis result was not sig� nificant (P = 0.367� �Table 5�.…”
Section: Discussionsupporting
confidence: 83%
“…The mean value of BMI was reported to be higher in those with severe OSA with significant difference from the non�severe OSA �P = 0.02�. 14,28 From our study however, the result showed otherwise �r 2 = 0.04, P = 0.28� �Table 4�. Kasey et al �2000� showed that while higher BMI were reportedly associated with severity of OSA, the severity of OSA however persists despite after this factor was elimi� nated.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…NC has been also related to various metabolic risk factors such as blood pressure and lipids [ 3 , 4 ], independent of overall adiposity (body mass index) and central obesity (waist circumference or visceral adipose tissue) [ 1 ]. It remains unclear whether these risk factors modify the relation between NC and IR [ 5 ].…”
Section: Introductionmentioning
confidence: 99%